Paraneoplastic eosinophilic dermatosis in a case of chronic lymphocytic leukemia - Chetan D Rajput; Balkrishna P Nikam; Shailesh S Malani (Wolters Kluwer Medknow Publications, 2019)
Eosinophilic dermatosis of hematologic malignancy is a rare paraneoplastic manifestation particularly associated with chronic lymphocytic leukemia (CLL).Clinically, it presents as a peculiar polymorphic pruritic eruption with characteristic histological findings of superficial and deep dense perivascular infiltrate of lymphocytes and eosinophils without any vasculitis. Although it has been reported intermittently with different names, there is paucity of reports of this condition in Indian literature. Here, we report a patient of CLL having insect bite-like eruptions nonresponsive to conventional therapy and confirmed as eosinophilic dermatosis on histology. Patient was having eruptions well before the diagnosis of malignancy, and intensity as well as frequency increased as the disease progressed. Good control over the disease was achieved using chemotherapy and steroids. Thus, this case explains diagnostic and prognostic significance of eosinophilic dermatosis in CLL.